Agricultural digitalization and rural development in COVID-19 response plans: A review article - Haggag, W. M. (International Journal of Agricultural Technology, 2021)
COVID-19 has led to spread economic adversity throughout the world since it effects on food security. After COVID-19 there is necessary to suggest the novel direction and combination of new input, information and telecommunication technologies for agricultural growth and development. Agricultural digitalization is able to impact rapidly to mitigate some of the negative effect of the COVID-19 pandemic. In developing countries, rural information and services are the most important of effective agricultural and development. The "Internet of Things" and electronic networks offer very promising technologies and many services and solutions including the agricultural fields. The application of digital technology is of great importance because it has the ability to provide technologies, innovations and acquired sustainability to the agricultural sector and increase productivity as an alternative and complement to agricultural extension. Mobile application have developed rapidly for enhancing telecommunication, information ,input , development , invention in service transmission and their quality. However, many stakeholders have known the need for digital agriculture. The most countries have already taken a national strategy for the agricultural sector’s use of information and communication technologies. These reviews explain the possibility of agricultural digitalization for rural services and development in COVID-19 response plans